Modern approaches to data assimilation in ocean modeling - Malanotte-Rizzoli, Paola, 1946- (Elsevier oceanography series, 1996)
The field of oceanographic data assimilation is now well established. The main area of concern of oceanographic data assimilation is the necessity for systematic model improvement and ocean state estimation. In this respect, the book presents the newest, innovative applications combining the most sophisticated assimilation methods with the most complex ocean circulation models. Ocean prediction has also now emerged as an important area in itself. The book contains reviews of scientific oceanographic issues covering different time and space scales. The application of data assimilation methods can provide significant advances in the understanding of this subject. Also included are the first, recent developments in the forecasting of oceanic flows. Only original articles that have undergone full peer review are presented, to ensure the highest scientific quality. This work provides an excellent coverage of state-of-the-art oceanographic data assimilation.